MEMBANGUN EKONOMI MIKRO MELALUI FIQH SOSIAL: Refleksi Pemikiran KH. M.A. Sahal Mahfudz - Nabil, Muhammad; Ismail , Muhammad (Jurnal Studi Islam dan Sosial, 2024)
This study is to examine the idea of bolstering Sahal Mahfudz's microeconomy in the micro, small, and medium-sized enterprise (MSME) sector, which provides context for Indonesia's poverty alleviation initiatives. This study employs a qualitative, explanatory research methodology, namely library research. The book Nuances of Social Fiqh and all of Sahal Mahfudz's publications—books, journals, papers, and so forth—were the main sources of data for this study. On the other hand, secondary sources are other scientific publications that are relevant to this study. As a result of this study, Sahal Mahfudz applies his theories to microeconomic issues in order to strengthen the microeconomy. The development of creativity and economic independence are the main goals. The next step is to give the community capital and training. Developing imaginative students, in order for them to grow as individuals. Not relying on ideological frameworks to produce autonomous, imaginative people and transforming the community's perspective on the paradigm shift from formalistic fiqh to socially nuanced fiqh.